Adequação da casa de saúde do índio de São Luís - MA ao contexto intercultural de seus usuários: organização, humanização e ambiência - DUAILIBE, Elza Galvão Bergê Cutrim (2015)
This study aimed to study the adequacy of service in the House of Indian Health in São Luís, MA (CASAI-SLZ) to the reality of its users based on the National Policy for the Health of Indigenous People (PNASPI) and Humanization National Policy (PNH). It is based on a qualitative methodology through a case study of exploratory and descriptive. Therefore, the research is referenced by means of studies on PNASPI and the PNH, considering issues related to its object, as ambience and interculturalism. The theoretical data were obtained in books, scientific articles, laws, ordinances and official publications that deal with indigenous health, as its historical and organization. We decided to first draw a picture on indigenous health policies in Brazil, considering the various changes in its management and then explain the roles of the Houses of Indian Health. Also analyzed the Humanization National Policy from the perspective of intercultural and fitness for indigenous peoples, highlighting the importance of ambience for couples. Field data collection used the method of semistructured interviews, and systematic observation, photographs and reports analysis assigned by the institution. The analysis identified problems in the implementation of health policies for indigenous peoples by the competent bodies and also by the Unified Health System and piecemeal management. The account of workers and CASAI-SLZ users pointed to problems in the physical and organizational structure as well as the lack of projects and humanizing actions, and services that are opposed to prescribing the applicable laws. The results indicated that, although the PNASPI and the PNH establish that indigenous have the right to special attention of that home conditions do not favor a fully based care in intercultural and specificity of its users. In addition to the difficulties identified in the house, they were also perceived problems in the health services of the Maranhão state and the management of the Indigenous Special Sanitary District of Maranhão that directly affect indigenous. The study was approved by the Special Indigenous Sanitary District of Maranhão (DSEI-MA) and by the Research Ethics Committee of the São Luís’s Health Municipal Secretary (CEPSEMUS).